Lectotypification of Themeda helferi Hack. (Andropogoneae, Poaceae) - Thomas S, Alan (Phytotaxa, 2019)
The genus Themeda Forssk. was first described by Forsskåhl in 1775 with Themeda triandra Forssk. (Veldkamp, 2016). Currently ca. 29 species were reported from different parts of the old world and the new world (POWO, 2019). Among them ca. 15 species were reported from India of which ca. five species are endemic (WCSP, 2019). Themeda helferi Hack. was recently reported from India (Anil Kumar et al., 2018). During the literature survey, it came to know that no one designated any lectotype as per the Shenzhen code Art. 9.3 or lacking requirements as per the Shenzhen code Art. 7.11 (Turland et al. 2018). Hence, in this communication, I am designating lectotype for this species.